Lumped flood routing through an interactive web application (LACCEI, 2024)
Lumped flood routing in reservoirs is a fundamental topic in introductory hydrology courses in engineering programs. Understanding the associated concepts is of great importance for their subsequent application in professional life, such as in the design and operation of reservoirs. Students often have difficulty understanding the relationships between variables, parameters, and limitations between methods. In turn, experience shows that students waste time on spreadsheet calculations, and consequently, learning of concepts is not prioritized. In this work, an application is developed that solves lumped flood routing in a reservoir, where various parameters such as reservoir characteristics, input hydrographs, and the dam discharge organ can be modified. The tool has an interface that allows the user to interact in a simple way, since by easily modifying the parameters, the effect on the result of the lamination can be graphically seen. This application is open source and is available for any device with internet access.